Incorporation of a metal-mediated base pair into an ATP aptamer – using silver(I) ions to modulate aptamer function - Heddinga, Marius H.; Müller, Jens (Beilstein Journal of Organic Chemistry, 2020)
For the first time, a metal-mediated base pair has been used to modulate the affinity of an aptamer towards its target. In particular, two artificial imidazole 2’-deoxyribonucleosides (Im) were incorporated into various positions of an established ATP-binding aptamer (ATP, adenosine triphosphate), resulting in the formation of three aptamer derivatives bearing Im:Im mispairs with a reduced ATP affinity. A fluorescence spectroscopy assay and a binding assay with immobilized ATP were used to evaluate the aptamer derivatives. Upon the addition of one Ag(I) ion per mispair, stabilizing Im–Ag(I)–Im base pairs were formed. As a result, the affinity of the aptamer derivative towards ATP is restored again. The silver(I)-mediated base-pair formation was particularly suitable to modulate the aptamer function when the Im:Im mispairs (and hence the resulting metal-mediated base pairs) were located close to the ATP-binding pocket of the aptamer. Being able to trigger the aptamer function opens new possibilities for applications of oligonucleotides.
Keywords: aptamer; ATP; bioinorganic chemistry; DNA; imidazole; metal-mediated base pairs

(untitled) - Famulok, M.; Hartig, J. S.; Mayer, G. (Chem. Rev., 2007)

(untitled) - Hermann, T.; Patel, D. J. (Science, 2000)

(untitled) - Wilson, D. S.; Szostak, J. W. (Annu. Rev. Biochem., 1999)

(untitled) - Keefe, A. D.; Pai, S.; Ellington, A. (Nat. Rev. Drug Discovery, 2010)

(untitled) - Liu, J.; Cao, Z.; Lu, Y. (Chem. Rev., 2009)

(untitled) - Tombelli, S.; Minunni, M.; Mascini, M. (Biosens. Bioelectron., 2005)

(untitled) - Willner, I.; Zayats, M. (Angew. Chem., Int. Ed., 2007)

(untitled) - Wang, S.; Yue, L.; Li, Z.-Y.; Zhang, J.; Tian, H.; Willner, I. (Angew. Chem., Int. Ed., 2018)

(untitled) - Shin, J.-S.; Pierce, N. A. (J. Am. Chem. Soc., 2004)

(untitled) - Del Grosso, E.; Ragazzon, G.; Prins, L. J.; Ricci, F. (Angew. Chem., Int. Ed., 2019)

(untitled) - Punt, P. M.; Clever, G. H. (Chem. Sci., 2019)

(untitled) - Lake, R. J.; Yang, Z.; Zhang, J.; Lu, Y. (Acc. Chem. Res., 2019)

(untitled) - Naskar, S.; Guha, R.; Müller, J. (Angew. Chem., Int. Ed., 2020)

(untitled) - Takezawa, Y.; Müller, J.; Shionoya, M. (Chem. Lett., 2017)

(untitled) - Müller, J. (Coord. Chem. Rev., 2019)

(untitled) - Santamaría-Díaz, N.; Méndez-Arriaga, J. M.; Salas, J. M.; Galindo, M. A. (Angew. Chem., Int. Ed., 2016)

(untitled) - Jash, B.; Müller, J. (Chem. – Eur. J., 2017)

(untitled) - Ukale, D. U.; Lönnberg, T. (Angew. Chem., Int. Ed., 2018)

(untitled) - Takezawa, Y.; Yoneda, S.; Duprey, J.-L. H. A.; Nakama, T.; Shionoya, M. (Chem. Sci., 2016)

(untitled) - Takezawa, Y.; Nakama, T.; Shionoya, M. (J. Am. Chem. Soc., 2019)

(untitled) - Nakama, T.; Takezawa, Y.; Sasaki, D.; Shionoya, M. (J. Am. Chem. Soc., 2020)

(untitled) - Engelhard, D. M.; Nowack, J.; Clever, G. H. (Angew. Chem., Int. Ed., 2017)

(untitled) - Saran, R.; Kleinke, K.; Zhou, W.; Yu, T.; Liu, J. (Biochemistry, 2017)

(untitled) - Saran, R.; Yao, L.; Hoang, P.; Liu, J. (Biochimie, 2018)

(untitled) - Huizenga, D. E.; Szostak, J. W. (Biochemistry, 1995)

(untitled) - Lin, C. H.; Patel, D. J. (Chem. Biol., 1997)

(untitled) - Wu, N.; Willner, I. (Nanoscale, 2017)

(untitled) - Yang, J.; Jiang, S.; Liu, X.; Pan, L.; Zhang, C. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Walter, H.-K.; Bauer, J.; Steinmeyer, J.; Kuzuya, A.; Niemeyer, C. M.; Wagenknecht, H.-A. (Nano Lett., 2017)

(untitled) - Johannsen, S.; Megger, N.; Böhme, D.; Sigel, R. K. O.; Müller, J. (Nat. Chem., 2010)

(untitled) - Petrovec, K.; Ravoo, B. J.; Müller, J. (Chem. Commun., 2012)

(untitled) - Tan, X.; Litau, S.; Zhang, X.; Müller, J. (Langmuir, 2015)

(untitled) - Hensel, S.; Megger, N.; Schweizer, K.; Müller, J. (Beilstein J. Org. Chem., 2014)

(untitled) - Léon, J. C.; She, Z.; Kamal, A.; Shamsi, M. H.; Müller, J.; Kraatz, H.-B. (Angew. Chem., Int. Ed., 2017)

(untitled) - Léon, J. C.; González-Abradelo, D.; Strassert, C. A.; Müller, J. (Chem. – Eur. J., 2018)

(untitled) - Naskar, S.; Hebenbrock, M.; Müller, J. (Inorg. Chim. Acta, 2020)

(untitled) - Verma, S.; Mishra, A. K.; Kumar, J. (Acc. Chem. Res., 2010)

(untitled) - Huard, D. J. E.; Demissie, A.; Kim, D.; Lewis, D.; Dickson, R. M.; Petty, J. T.; Lieberman, R. L. (J. Am. Chem. Soc., 2019)

(untitled) - Vorlíčková, M.; Kejnovská, I.; Bednářová, K.; Renčiuk, D.; Kypr, J. (Chirality, 2012)

(untitled) - Nutiu, R.; Li, Y. (J. Am. Chem. Soc., 2003)

(untitled) - Kondo, J.; Tada, Y.; Dairaku, T.; Hattori, Y.; Saneyoshi, H.; Ono, A.; Tanaka, Y. (Nat. Chem., 2017)

(untitled) - Zhao, H.; Leonard, P.; Guo, X.; Yang, H.; Seela, F. (Chem. – Eur. J., 2017)

(untitled) - Funai, T.; Miyazaki, Y.; Aotani, M.; Yamaguchi, E.; Nakagawa, O.; Wada, S.-i.; Torigoe, H.; Ono, A.; Urata, H. (Angew. Chem., Int. Ed., 2012)

(untitled) - Sassanfar, M.; Szostak, J. W. (Nature, 1993)